Analisis Pengelolaan Koleksi Grey Literatur di Perpustakaan - Kiki, Riski Diana; Mulyadi, Mulyadi (UIN Raden Intan Lampung, 2023)
The purpose of this study was to find out how to manage the gray literature collection, both theses, theses and dissertations at the UIN Raden Fatah Palembang Library. The method used in this article is a qualitative method with a case study approach, with the technique of collecting observations and literature sources. The results of this article show the management of the gray literature collection (thesis, thesis and dissertation) at the UIN Raden Fatah Palembang Library. Where in the thesis library, theses and accompanied by alumni students or students who have just distributed theses, theses and dissertations must be managed first so that information retrieval for students who need references can be easily found. And the management of the gray literature collection has been carried out with the available resources, and the management system is structured from tasting, recording, class, inputting, labeling and giving colors according to the presentation and placement of theses, theses and dissertations according to the shelves of each study program. However, the management still needs improvement in several aspects, such as facilities such as lacking library shelves, networks and chips to detect if the thesis is taken or stolen.